On the shape of cicada’s wing leading-edge cross section - Rachel M. Starkweather (Nature Portfolio, 2021)
Abstract An important role that the leading-edge cross-section shape plays in the wing flight performance is well known in aeronautics. However, little is known about the shape of the leading-edge cross section of an insect’s wing and its contribution to remarkable qualities of insect flight. In this paper, we reveal, in the first time, the shape of the leading-edge cross section of a cicada’s wing and analyze its variability along the wing. We also identify and quantify similarities in characteristic dimensions of this shape in the wings of three different cicada species.